Coping strategies for handling stress and providing mental health in elite athletes: a systematic review - Nuetzel, B. (Frontiers in Sports and Active Living, 2023)
Background: The combination of stressors unique to the athletic context plus the sensitive developmental phase that elite athletes go through during their peak performance may increase the athletes` vulnerability to mental health decrements. To emphasize the necessity to raise elite athletes' awareness of health risks, it seems to be essential to teach them coping skills to handle stress and to make affected athletes aware of how to recognize, evaluate, and articulate potential risks to their health.